2020
DOI: 10.3390/cancers12051276
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a Novel Liquid Fiducial Marker, BioXmark®, for Small Animal Image-Guided Radiotherapy Applications

Abstract: BioXmark® (Nanovi A/S, Denmark) is a novel fiducial marker based on a liquid, iodine-based and non-metallic formulation. BioXmark® has been clinically validated and reverse translated to preclinical models to improve cone-beam CT (CBCT) target delineation in small animal image-guided radiotherapy (SAIGRT). However, in phantom image analysis and in vivo evaluation of radiobiological response after the injection of BioXmark® are yet to be reported. In phantom measurements were performed to compare CBCT imaging a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(29 citation statements)
references
References 48 publications
0
29
0
Order By: Relevance
“…did the same in pancreatic tumors [29] . In vivo measurements of the stability of the marker over a 5-month period showed movement of less than 2 mm [30] . Hence, fiducial markers may provide a potential benefit in gastrointestinal tumors to allow for precise day-to-day position verification.…”
Section: Discussionmentioning
confidence: 96%
“…did the same in pancreatic tumors [29] . In vivo measurements of the stability of the marker over a 5-month period showed movement of less than 2 mm [30] . Hence, fiducial markers may provide a potential benefit in gastrointestinal tumors to allow for precise day-to-day position verification.…”
Section: Discussionmentioning
confidence: 96%
“…Some developments have been made with the implementation of iodinated and nanoparticle-based contrast agents which have dual benefits of enhancement of CT image contrast and therapeutic dose deposition [4] , [28] . Some studies (2%) have also shown the possibility of improved targeting accuracy of low contrast tissues using fiducial markers for treatment alignment [29] .…”
Section: Discussionmentioning
confidence: 99%
“…Liquid fiducial markers have the additional advantage of minimizing migration over time ( 6 , 7 ) and minimizing any image artifacts ( 8 , 9 ). Previous studies have further indicated that liquid fiducials are safer and easier to inject at the targeted site compared to solid fiducials that may require endoscopic implantation, which may be more complex for resource-limited settings and may be uncomfortable procedure for the patient ( 10 , 11 ). Recent studies have highlighted the use of liquid fiducials to improve image-guided radiotherapy in different types of tumors e.g.…”
Section: Introductionmentioning
confidence: 99%